Unconditional Basic Income: An Economic Perspective - Luke Haywood (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
A wide range of public figures from the social sciences, politics and business have proposed paying every citizen a fixed amount of income without means testing or work requirement. The idea is fascinating. Most recently, a widely reported crowd-funding initiative from Berlin collected EUR12,000 to finance one year's worth of unconditional basic income for a randomly selected individual. – – Eine Reihe von Persönlichkeiten aus Wissenschaft, Politik und Unternehmertum unterstützen die Idee eines bedingungslosen Einkommens für jeden Bürger, das unabhängig von Vermögen und Bereitschaft zu Erwerbsarbeit gezahlt wird. Die Idee fasziniert. So schaffte es eine Initiative aus Berlin jüngst, medienwirksam 12.000 EUR zu sammeln, um einer zufällig ausgewählten Person ein Jahr ein bedingungsloses Grundeinkommen (BGE) zu finanzieren.
Keywords: 330